The Ruegeria pomeroyi acuI Gene Has a Role in DMSP Catabolism and Resembles yhdH of E. coli and Other Bacteria in Conferring Resistance to Acrylate - Todd, Jonathan D.; Curson, Andrew R. J.; Sullivan, Matthew J.; Kirkwood, Mark; Johnston, Andrew W. B. (PLOS ONE, 2012)
The Escherichia coli YhdH polypeptide is in the MDR012 sub-group of medium chain reductase/dehydrogenases, but its biological function was unknown and no phenotypes of YhdH− mutants had been described. We found that an E. coli strain with an insertional mutation in yhdH was hyper-sensitive to inhibitory effects of acrylate, and, to a lesser extent, to those of 3-hydroxypropionate. Close homologues of YhdH occur in many Bacterial taxa and at least two animals. The acrylate sensitivity of YhdH− mutants was corrected by the corresponding, cloned homologues from several bacteria. One such homologue is acuI, which has a role in acrylate degradation in marine bacteria that catabolise dimethylsulfoniopropionate (DMSP) an abundant anti-stress compound made by marine phytoplankton. The acuI genes of such bacteria are often linked to ddd genes that encode enzymes that cleave DMSP into acrylate plus dimethyl sulfide (DMS), even though these are in different polypeptide families, in unrelated bacteria. Furthermore, most strains of Roseobacters, a clade of abundant marine bacteria, cleave DMSP into acrylate plus DMS, and can also demethylate it, using DMSP demethylase. In most Roseobacters, the corresponding gene, dmdA, lies immediately upstream of acuI and in the model Roseobacter strain Ruegeria pomeroyi DSS-3, dmdA-acuI were co-regulated in response to the co-inducer, acrylate. These observations, together with findings by others that AcuI has acryloyl-CoA reductase activity, lead us to suggest that YdhH/AcuI enzymes protect cells against damaging effects of intracellular acryloyl-CoA, formed endogenously, and/or via catabolising exogenous acrylate. To provide “added protection” for bacteria that form acrylate from DMSP, acuI was recruited into clusters of genes involved in this conversion and, in the case of acuI and dmdA in the Roseobacters, their co-expression may underpin an interaction between the two routes of DMSP catabolism, whereby the acrylate product of DMSP lyases is a co-inducer for the demethylation pathway.